2011
DOI: 10.1007/jhep05(2011)024
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: two experiments for the price of one? The role of the second oscillation maximum in long baseline neutrino experiments

Patrick Huber,
Joachim Kopp

Abstract: We investigate the quantitative impact that data from the second oscillation maximum has on the performance of wide band beam neutrino oscillation experiments. We present results for the physics sensitivities to standard three flavor oscillation, as well as results for the sensitivity to non-standard interactions. The quantitative study is performed using an experimental setup similar to the Fermilab to DUSEL Long Baseline Neutrino Experiment (LBNE). We find that, with the single exception of sensitivity to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…However, in Ref. [53] it was shown that for a wide-band beam, the significantly lower statistics present at the second oscillation peak due to the smaller flux (typically at the tail) and cross section (at lower energies), combined with the large background from NC interactions migrating from higher energies, rendered the information coming from the second peak nearly irrelevant (see also [54]) 1 . Thus, an improved energy reconstruction can be beneficial to the search for leptonic CP violation in two ways.…”
Section: Resultsmentioning
confidence: 99%
“…However, in Ref. [53] it was shown that for a wide-band beam, the significantly lower statistics present at the second oscillation peak due to the smaller flux (typically at the tail) and cross section (at lower energies), combined with the large background from NC interactions migrating from higher energies, rendered the information coming from the second peak nearly irrelevant (see also [54]) 1 . Thus, an improved energy reconstruction can be beneficial to the search for leptonic CP violation in two ways.…”
Section: Resultsmentioning
confidence: 99%
“…Hyper-Kamiokande [129,130] is an interesting proposal that expects to improve the sensitivity to NSI, by using the atmospheric neutrino data [131,132,133]; their expectations for the normal hierarchy case are particularly appealing. On the other hand, for the case of the LBNE [134] and LBNO [135] proposals, the expected sensitivity to NSI is also encouraging, especially for the flavor changing case of µτ and eµ [136].…”
Section: Perspectives For Nsi In Propagationmentioning
confidence: 91%
“…While non-standard neutrino interactions may affect the neutrino production and detection processes, here we only consider the effects of the new interactions during neutrino propagation, as including these effects requires additional parameters describing the production and detection processes (see, for example, Refs. [40,41]). The use of a near detector in experiments will help address these effects (see, for example, Ref.…”
Section: Formalism Current Bounds and Oscillation Probabilitiesmentioning
confidence: 99%